PHENOLIC COMPOUNDS, CAROTENOIDS, TOCOPHEROLS AND FATTY ACIDS PRESENT IN OILS EXTRACTED FROM PALM FRUITS - COIMBRA, MICHELE CARDOSO; JORGE, NEUZA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2013)
This review aimed to discuss the main bioactive compounds present in oils extracted from palm trees, indicating possible applications for the same. The bioactive compounds approached were: phenolic compounds, carotenoids, tocopherols, mono and polyunsaturated fatty acids. It is growing the search for food, especially from plant origin, characterized by the presence of such substances due to their benefits. Many studies show palm species as important sources of bioactive compounds and essential fatty acids. Therefore it is important to study the fruit characterization and composition of the oil from palm species of different regions that are still poorly investigated, seeking the possibility of its application in industry or the development of functional foods.